The malaise of inability - Antón, Maria Rita Martínez (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
The occupational therapy, as long as therapy, involves the offer of an answer to demand of malaise treatment. Social demand of problem resolution passes through any treatment form, since the delegation that authorizes their practice (professional education, certification, etc.). But also the singular subjective demands of reduction ffom suffering do it. The definition of what is the malaise to treat will define different offers and interventions. The analysis of some of the demands attended by the discipline proposes a discussion of a treatment of a malaise offered by occupational therapy practice from the notion of inability.